Herpes simplex encephalitis and pseudotumour cerebri due to isotretinoin - Varoglu, Asuman Orhan; Aksoy, Asude (Pakistan Medical Assoc, 2018)
Isotretinoin can have significant adverse reactions on multiple systems. We report a unique case of pseudotumour cerebri and herpes encephalitis resulting due to isotretinoin. A 19-year-old female patient was admitted to our clinic, presenting with headache, nausea, vomiting and fever since three days. She had used isotretinoin for the last two months. The patient's neurological examination revealed the presence of neck stiffnes and a body temperature of 39,0 degrees C. MRI showed high signal localized to the temporal lobe and insula on the right and widened cerebrospinal fluid signal intensity on either side of the optic nerve. Electroencephalogram sharp and wave paroxysms on the right temporo-parietal region. Lumbar puncture showed an opening pressure of 320 mm H2O. The cerebrospinal fluid displayed the presence of 4-5 lymphocytes. On these grounds, the diagnosis of pseudotumour cerebri and herpes encephalitis was made. It is thus suggested that the physicians must keep in mind that pseudotumour cerebri and herpes encephalitis are possible adverse effects of isotretinoin.
Keywords: isotretinoin; pseudotumor cerebri; herpes simplex encephalitis; side effect